Medico-legal evaluation of torture victims in the USA before the Istanbul Protocol - Quiroga, Jose; Deutsch, Ana (Torture Journal, 2023)
The article reviews the historical precedents of the Forensic Assessment of Torture Survivors in the US in the 1970s and 1980s, setting the precedents of the US branch of the construction of the Istanbul Protocol that was developed in the late 1990s. It includes, as supplementary material, the first model of affidavit developed in Los Angeles at that time, which is the first predecessor in the history of the Istanbul Protocol in the US. Similar models were developed in Latin America, Canada and Turkey. All these efforts were later joined under the United Nations auspices in what finally ended to be the Istanbul Protocol.